2007
DOI: 10.1002/hep.21934
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil prevents sucrose-induced fatty liver but exacerbates high-safflower oil-induced fatty liver in ddy mice

Abstract: Diets high in sucrose/fructose or fat can result in hepatic steatosis (fatty liver). We analyzed the effects of dietary fish oil on fatty liver induced by sucrose, safflower oil, and butter in ddY mice. In experiment I, mice were fed a high-starch diet [70 energy% (en%) starch] plus 20% (wt/wt) sucrose in the drinking water or fed a high-safflower oil diet (60 en%) for 11 weeks. As a control, mice were fed a high-starch diet with drinking water. Fish oil (10 en%) was either supplemented or not. Mice supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
(36 reference statements)
4
36
0
2
Order By: Relevance
“…As suggested by our previous studies (18)(19)(20), a marked increase in postprandial TG concentrations after being fed a HF diet was observed in ddY mice but not in C57BL/6J mice. Mice were fed a standard laboratory chow and fasted for 24 h and then allowed to freely eat a HF diet (60% energy from saffl ower oil).…”
Section: An Increase In Postprandial Tg Concentrations In Ddy Micesupporting
confidence: 53%
See 1 more Smart Citation
“…As suggested by our previous studies (18)(19)(20), a marked increase in postprandial TG concentrations after being fed a HF diet was observed in ddY mice but not in C57BL/6J mice. Mice were fed a standard laboratory chow and fasted for 24 h and then allowed to freely eat a HF diet (60% energy from saffl ower oil).…”
Section: An Increase In Postprandial Tg Concentrations In Ddy Micesupporting
confidence: 53%
“…by guest, on March 28, 2019 www.jlr.org Downloaded from in the SREBP-1c promoter and show hepatic steatosis when fed sucrose supplementation or a HF diet ( 19 ). Mice with guanine at this site show increased liver SREBP-1c mRNA in response to a high-fructose diet, whereas mice with adenine, such as C57BL/6J mice, do not ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the up-regulation of Cd36, which mediates fatty acid uptake from the circulation. Studies in mice 25,47 indicated that Cd36 plays a crucial role in the transport of fatty acid in hepatocytes and hence regulates the hepatic triacylglycerol concentration. We previously observed that sesame lignan decreased hepatic concentration of triacylglycerol in rats fed a saturated fat palm oil 16,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…These actions have been shown to be mediated through the downregulation of SREBP-1 expression (Sekiya et al, 2003;Yamazaki et al, 2007). In addition, it is reported that PUFA can suppress SOAT-2 expression in experimental animals (Botham et al, 2001;Lecker et al, 2011).…”
Section: ꮅꮆꮉꮄꭸꮃmentioning
confidence: 98%
“…Notably, the oleic acid (18:1n-9)-containing CE level was markedly elevated in the liver of mice fed the CAHF diet compared with in the liver of those fed the normal diet (Watanabe and Tsuneyama, 2012). On the other hand, the administration of fish oil or its major n-3 polyunsaturated fatty acids (PUFA) is effective in attenuating hepatic steatosis in experimental animals (Hein et al, 2010;Jung et al, 2011;Kajikawa et al, 2009;Sekiya et al, 2003;Tanaka et al, 2010;Yamazaki et al, 2007). Moreover, n-3 PUFA administration could prevent the hepatic accumulation of TG through the suppression of monounsaturated fatty acids (MUFA) generation (Kajikawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%